Adverse Effects of Antidepressants for Chronic Pain: A Systematic Review and Meta-analysis - Riediger, Carina; Schuster, Tibor; Barlinn, Kristian; Maier, Sarah; Weitz, Jürgen; Siepmann, Timo (Frontiers in Neurology, 2017)
Background: Antidepressants are widely used in the treatment of chronic pain. Applied doses are lower than those needed to unfold an antidepressive effect. While efficacy of antidepressants for chronic pain has been reported in large randomized controlled trials, there is inconsistent data on adverse effects and tolerability. We aimed at synthesizing data from randomized controlled trials to explore adverse effect profiles and tolerability of antidepressants for treatment of chronic pain. Methods: Systematic literature research and meta-analyses were performed regarding side effects and safety of different antidepressants in the treatment of chronic pain according to PRISMA guidelines. The National Center for Biotechnology Information library and MEDLINE were searched. Randomized placebo-controlled trials were included in quantitative data synthesis. Results: Out of 1975 screened articles, 33 papers published between 1995 and 2015 were included in our review and 23 studies were included in the meta-analyses. A higher risk for adverse effects compared to placebo was observed in all antidepressants included in our analyses, except nortriptyline. The most prevalent adverse effects were dry mouth, dizziness, nausea, headache and constipation. Amitriptyline, mirtazapine, desipramine, venlafaxine, fluoxetine and nortriptyline showed the highest placebo effect-adjusted risk of adverse effects. Risk for withdrawal due to adverse effects was highest in desipramine (risk ratio: 4.09, 95%-CI [1.31; 12.82]) followed by milnacipran, venlafaxine and duloxetine. The most common adverse effects under treatment with antidepressants were dry mouth, dizziness, nausea, headache and constipation followed by palpitations, sweating and drowsiness. However, overall tolerability was high. Each antidepressant showed distinct risk profiles of adverse effects. Conclusion: Our synthesized data analysis confirmed overall tolerability of low dose antidepressants for the treatment of chronic pain and revealed drug specific risk profiles. This encompassing characterization of adverse effect profiles might be useful in defining multimodal treatment regimens for chronic pain which also consider patients’ comorbidities and co-medication.